Embolisation of External Jugular Vein Aneurysm: A Case Report - Rajadurai, Arvin (Malays J Med Sci, 2017)
INTRODUCTION: Venous aneurysms are not as common as their arterial counterpart. The choice of management is debatable. Case Report: We present the case of a teenage boy with left external jugular vein aneurysm treated by endovascular technique. Embolisation was done using pushable microcoils with access via the femoral vein and direct puncture. CONCLUSION: This form of treatment provides a less-invasive option with a more concrete evaluation of the venous abnormality and its drainage during venous aneurysm occlusion.